Readmissions in emergency service: morbidity profile of the patients - Mariana Ferreira Borges; Ruth Natalia Teresa Turrini (Rev Rene)
A retrospective study was conducted from hospital records of patients admitted to the emergency service of a philanthropic teaching hospital of high level of attention in São Paulo city (Brazil) over the year 2003, in order to analyze the readmissions. Data were analyzed by measures of central tendency and variability, Mann Whitney test and analysis of survival times (Kaplan-Meier). Of the total admissions, 714 (12.6%) were readmissions which occurred in all ages with an increase being observed after age 40 years, especially after age 80 years. Diseases as anemia, endocrine and neoplasms were the main cause of readmission. The diagnoses in first-admission and its relation with the readmission diagnoses influenced the frequency of readmissions. It was observed that age and diagnoses had a statistically significant effect on readmissions (p<0,005). The diagnoses diabetes, hypertension, medical complications and pneumonias showed that some readmissions were potentially avoidable.